2022
DOI: 10.1590/2175-7860202273086
|View full text |Cite
|
Sign up to set email alerts
|

Does shading mitigate water restriction in Ormosia arborea seedlings?

Abstract: This study aimed to evaluate the potential of shading in reducing the stressful effect of water restriction on photosynthetic and antioxidant metabolism, favoring the growth of Ormosia arborea seedlings and the recovery metabolic. The shadings levels studied were: 0, 30 and 70%. Two water regimes were implemented: control, in which the plants were irrigated at 75% of soil water retention capacity and water restriction, in which the irrigation was suspended until the photosynthetic rate reached values close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…The increase in leaf area under conditions of lower solar radiation can be considered phenotypic plasticity, as the increase in leaf area optimizes the interception of light rays and thus results in more efficient production of photoassimilates (Poorter et al, 2019;Reis et al, 2022;Silva et al, 2022). Furthermore, during the evaluations, we observed that plants with low water availability showed a reduction in leaf area, which remained stable even after supplying a greater amount of water, as observed in REC.…”
Section: Discussionsupporting
confidence: 55%
“…The increase in leaf area under conditions of lower solar radiation can be considered phenotypic plasticity, as the increase in leaf area optimizes the interception of light rays and thus results in more efficient production of photoassimilates (Poorter et al, 2019;Reis et al, 2022;Silva et al, 2022). Furthermore, during the evaluations, we observed that plants with low water availability showed a reduction in leaf area, which remained stable even after supplying a greater amount of water, as observed in REC.…”
Section: Discussionsupporting
confidence: 55%